Participation as a medium of empowerment in community development. - Nikkhah, Hedayat Allah; Redzuan, Ma’rof (EuroJournals, 2009)
This paper elucidates the relationship between approaches of community development, participation and empowerment. Participation and empowerment are two important concepts of community development. The final goal of community development is empowering the communities and improving the quality of their lives. But, it is impossible to achieve this goal without participation and involvement of the community in particular projects. On the other hand, there are many definitions, types and models of participation. Thus, the questions are: what type of participation that leads to empowerment? Do every type and model of participation leads to empowerment? This paper emphasizes on participation as a mean and participation as an end. It will try to demonstrate that which types of this participation that can lead to empowerment. Since in participation as an end people directly involve in the project and they can take the control of decision that affect on their lives, it is concluded that participation as an end would leads to empowerment. Furthermore, there are many approaches in community development, namely top-down, bottom-up and partnership. Finally, this paper concludes that empowerment and type of participation as an end in bottom-up approach of community development will be high, and consequently the particular community will access to a sustainable development.